Blood pressure, cholesterol and cardiovascular disease in Thailand. Issue 1 (11th July 2010) - Khonputsa, Panrasri; Veerman, J Lennert; Vathesatogkit, Prin; Vanavanan, Somlax; Lim, Stephen; Bertram, Melanie; Vos, Theo; Ratanachaiwong, Wipa; Yamwong, Sukit
Abstract : Background: Although associations between risk factors such as hypertension and hypercholesterolaemia, and cardiovascular disease (CVD) are well-established it is not known to what extent these associations are similar in people from different ethnicities or regions. This study aims to measure the contributions of systolic blood pressure (SBP) and total cholesterol (TC) to ischaemic heart disease (IHD) and stroke in the Thai population. Methods and results: Data from a Thai cohort study were used for analyses. Participants were 2702 males and 797 females aged between 35 and 54 years at the start of study in 1985. Cox Proportional Hazards Models were used to assess RRs of IHD or stroke associated with SBP or TC stratified by age at the time of an event of 30–44, 45–59, and 60–69 years. During the 17 years of follow-up, 96 IHD (40 non-fatal, 56 fatal), 69 strokes (32 non-fatal and 37 fatal) occurred. Each 1 mmol/l increase in TC was associated with a fivefold increase in IHD risk in people aged 30–44 years, but not with significant increase in stroke risk in any age group. The RRs (95% CIs) of IHD per 10 mm Hg increase in SBP were 1.31 (1.04 to 1.64) and 1.46 (1.15 to 1.87), and of stroke, 1.40 (1.10 to 1.79) and 1.85 (1.40 to 2.45) in people aged 45–59 and 60–69 years, respectively. Conclusions: Increases in IHD and stroke risks associated with these two risk factors observed in Thailand are comparable with those in the Asia Pacific and western populations.